2021
DOI: 10.3389/fimmu.2021.670398
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Associated With Anti-IL-23 Agents: Clinical Evidence and Possible Mechanisms

Abstract: BackgroundAnti-interleukin (IL)-23 agents are widely used for autoimmune disease treatment; however, the safety and risks of specific symptoms have not been systematically assessed.ObjectivesThe aim of this study was to summarize the characteristics and mechanisms of occurrence of five immunological and non-immunological adverse events caused by different anti-IL-23 agents.MethodsThe Cochrane Library, EMBASE, PubMed, and Web of Science databases were searched for eligible randomized clinical trials published f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 71 publications
1
9
0
1
Order By: Relevance
“…Compared with traditional therapies, although biological agents have good curative effects, the risk of recurrence is increased. A recently published meta-analysis showed that anti-IL-23 drugs are likely to cause a series of immunological and non-immunological adverse events, while their long-term use may cause mental illness ( 8 ). Therefore, dermatologists are always seeking better treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional therapies, although biological agents have good curative effects, the risk of recurrence is increased. A recently published meta-analysis showed that anti-IL-23 drugs are likely to cause a series of immunological and non-immunological adverse events, while their long-term use may cause mental illness ( 8 ). Therefore, dermatologists are always seeking better treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-IL-23 agents are widely used to treat various autoimmune conditions like CD, ulcerative colitis, psoriasis and ankylosing spondylitis. Compared with anti-IL-23-p19 agents, anti-IL12/23-p40 agents are associated with more adverse effects and more frequently lead to cardiovascular events 22. Although the relationship between anti-IL-12/23-p40 agents and SCEs remains unclear, this rare case of HF after initiation of ustekinumab serves as an important data point in determining that relationship; clinicians should consider this in the differential while this relationship continues to be explored.…”
Section: Discussionmentioning
confidence: 98%
“…BAs are highly active immunologic agents that exert their effects by blocking specific inflammatory factors produced by the immune system. BAs are commonly used in the treatment of autoimmune diseases such as rheumatoid arthritis, PSA, systemic lupus erythematosus, and ankylosing spondylitis ( 5 ). In 2004, the European Medicines Agency (EMA) approved the first BA, etanercept; adalimumab and ustekinumab have since emerged ( 6 ).…”
Section: Introductionmentioning
confidence: 99%